ENHANING EFFICIENCY IN ITR FILING USING EASY OFFICE: AN INTERNSHIP STUDY AT CA SIRAJ MAVANI AND ASSOCIATES - Lakhani, Suzan; Shewale, Bhojraj; Sharma, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
Filing of ITR in India is gradually shifting to more digital platforms, enabling quicker processing with minimum manual errors. This research paper aims to find out how digital software, namely Easy Office, influences the efficiency in ITR filing at a CA firm. The study is done based on the observation during my 4 weeks of internship at a CA firm where I alone filed around 5-10 ITR’s using Easy Office. Easy Office is integrated directly with the Income Tax Portal and allows auto fetching and cross verification of taxpayer data from multiple sources. The software supports: • Importing Form 16: The system allows direct uploads of Part A and Part B PDFs. It auto-reads things such as gross salary, deductions under Chapter 5-A, and TDS. The software pre-populates all salary fields into the ITR form, reducing manual entry errors. • AIS Sync: Easy Office connects to the AIS portal and fetches financial information reported by banks, mutual funds, and other institutions. This helps ensure that all the reported income sources are correctly reflected in the return to avoid mismatch notices. • TIS: Taxpayer Information Summary Easy Office automatically matches AIS with TIS instead of manually comparing data and highlights mismatches that may trigger a notice. • Form 26 AS (AS – 26) Fetch: The form fetches directly the data on tax credit (TDS/TCS) from TRACES. Once all the data is generated, the software pulls a pre-generated JSON file, validates it, and it’s ready to upload on the Income Tax portal. Personally, I handled 5-10 ITRs a day and took much less time than doing it manually.